A Case-Control Study of the Association Between the SPP1 Gene SNPs and the Susceptibility to Breast Cancer in Guangxi, China - Liang, Lina; Lu, Guanming; Guogang Pan, Guogang; Deng, Yibin; Liang, Jiadong; Liang, Limei; Liu, Jia; Tang, Yujin; Wei, Gui-Jiang (Frontiers in Oncology, 2019)
Secreted phosphoprotein-1 (SPP1) has been reported to be involved in the pathogenesis of breast cancer (BRC), but the influence of SPP1 SNPs on the BRC susceptibility has been rarely reported. In this study, we explored the association between rs11730582, rs2853750 and rs35893069 in the SPP1 gene and the BRC susceptibility. We used Snapshot assay to detect SPP1 SNPs in 471 BRC patients and 471 controls. The plasma SPP1 level was measured by enzyme-linked immunosorbent assay (ELISA). We found that the CC genotype and C allele ofHowever, there was no significant association between rs2853750 or rs35893069 and the BRC risk. In summary, our study found the association between rs11730582 and the risk of BRC and suggested rs11730582 may promote the occurrence and development of BRC by regulating SPP1 expression.